Care with Nature’s Cure: Herbal Drugs - Inamdar, Nazma; Edalat, Shima; B.Kotwal, Vikram; Pawar, Sunita (Pharmacognosy Reviews)
The acceptance and recognition of herbal medicine is increasing day by day. One of the important reason in increasing this interest is the perception of natural remedies being somehow more efficacious and less harmful that synthetic chemicals. This perception is not exactly true. In this review article, we have discussed several popular herbs and tried to provide a comprehensive review that summarizes adverse effects of herbal remedies. For being vigilant about the adverse effects one must have sufficient data and information about safety parameters. The hurdles in evaluating the safety of herbal drugs are lack of standardization, insufficient quality control and overall under reporting. The challenges posed in evaluating and improving safety of herbal drugs are need of standardization and quality control, availability of official compendia, dissemination of information, additional research, pharmacovigilance and need of regulation. With concentric efforts to surmount these challenges, the wealth of traditional knowledge will be put to judicious use in the form of herbal remedies and will be awarded with their rightful place in the health care system.
Keywords: Adverse Effects; Standardization; Quality Control; Regulations